Chromosome Telomere Integrity of Human Solid Neoplasms - Butler, Merlin G. (Cancer Genet Cytogenet, 1996)
Eukaryotic chromosomes contain specialized structures at the termini called telomeres. This region of DNA is required for replication and stability of the chromosome. Telomere reduction can contribute to genetic instability and has been described in certain malignancies (e.g., colon, leukemia, giant cell tumor of bone). To determine whether telomere reduction is a generalized phenomenon in malignancies, the telomere integrity of genomic DNA isolated from tumor cells was determined from 39 individuals with 15 different malignancies categorized as musculoskeletal, epithelial, cranial, or other, and peripheral blood leukocytes from the same patient, when possible, or age-matched controls. Significant telomere reduction occurred randomly across histopathologic groups including giant cell tumor of bone, glioblastoma, colon cancer, and Wilms’ tumor while telomere elongation occurred in chrodoma. The other remaining 10 malignancies did not show significant differences in telomere lengths compared with controls.